Aceh history, politics, and culture - Graf, Arndt; Schröter, Susanne; Wieringa, Edwin Paul; Institute of Southeast Asian Studies (Singapore Institute of Southeast Asian Studies, 2010)
The process of post-tsunami recovery and reconstruction in Aceh will take considerable time and is not easy. This book is an attempt at providing helpful background information on Acehnese history, politics and culture, which would benefit expatriate aid workers as well as foreign and domestic scholars in their dealings with the people of Aceh. It is written by specialists of Indonesian and Acehnese studies from a number of countries, together with Acehnese scholars. As the region was not accessible for decades, this book represents in many aspects a new, pioneering endevour in Acehnese studies. The chapters cover many important aspects of history, such as the female Sultanahs of Aceh, Aceh's Turkish connection and the Dutch Colonial War in Aceh. The main emphasis of the book is on relevant contemporary developments in the economy, politics, Islam, and the media, as well as painting, music, and literature.
Includes bibliographical referenfces (pages [343]-370) and index.
Keywords: Islam and culture -- Indonesia -- Aceh; Aceh (Indonesia) -- History; Aceh (Indonesia) -- Politics and government; Aceh (Indonesia) -- Economic conditions